2020
DOI: 10.2174/1874210602014010681
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Fracture Strength of Remaining Tooth Structure after Endodontic Treatment with Various Access Cavity Preparation Techniques

Abstract: Background: A perfect balance needs to be maintained between various types of endodontic access cavity preparation designs like - Traditional and conservative designed preparation to have access to the root canal system for proper cleaning and shaping of root canals without compromising the fracture resistance of the tooth structure. Aims and Objectives: We aimed to assess as well as draw comparisons of resistance aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…One of the most important methodological aspects of research design is the creation of a reliable baseline inasmuch as anatomical discrepancies of sampling may have a direct impact on the outcome. Although it seems logical that a proper anatomical pairing of teeth allocated for each experimental group may compromise the final conclusions, several studies performed sample selection based only on two‐dimensional radiographs (Corsentino et al, 2018; Krishan et al, 2014; Moore et al, 2016), external measurement of teeth (Corsentino et al, 2018; Ivanoff et al, 2017; Marinescu et al, 2020; Maske et al, 2021; Özyürek et al, 2017; Plotino et al, 2017; Roperto et al, 2019; Saberi et al, 2020; Sabeti et al, 2018; Spicciarelli et al, 2020) or merely by random allocation into the experimental groups (Chlup et al, 2017; Makati et al, 2018; Mustafa et al, 2020; Reddy et al, 2020). To overcome these sampling limitations, De‐Deus et al (2020) demonstrated that micro‐CT technology is the recommended method to pair‐match extracted teeth based on their anatomical characteristics (Figure 24).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most important methodological aspects of research design is the creation of a reliable baseline inasmuch as anatomical discrepancies of sampling may have a direct impact on the outcome. Although it seems logical that a proper anatomical pairing of teeth allocated for each experimental group may compromise the final conclusions, several studies performed sample selection based only on two‐dimensional radiographs (Corsentino et al, 2018; Krishan et al, 2014; Moore et al, 2016), external measurement of teeth (Corsentino et al, 2018; Ivanoff et al, 2017; Marinescu et al, 2020; Maske et al, 2021; Özyürek et al, 2017; Plotino et al, 2017; Roperto et al, 2019; Saberi et al, 2020; Sabeti et al, 2018; Spicciarelli et al, 2020) or merely by random allocation into the experimental groups (Chlup et al, 2017; Makati et al, 2018; Mustafa et al, 2020; Reddy et al, 2020). To overcome these sampling limitations, De‐Deus et al (2020) demonstrated that micro‐CT technology is the recommended method to pair‐match extracted teeth based on their anatomical characteristics (Figure 24).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…After using a strict selection criterion, specimen preparation for the fracture test is also a critical step that may affect the experimental results. In some studies, different types of occlusal cavities were prepared prior to accessing the pulp chamber in an effort to simulate a common clinical scenario observed in teeth referred for endodontic treatment (Abou‐Elnaga et al, 2019; Corsentino et al, 2018; Ivanoff et al, 2017; Mustafa et al, 2020; Özyürek et al, 2017; Reddy et al, 2020) (Table 5). Mustafa et al (2020) reported greater fracture resistance of teeth with ConsAC than TradAC only when teeth had two residual walls, while no difference was observed in the presence of three residual walls.…”
Section: Current Evidence Of Minimal Cavities On the Fracture Resista...mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of ex vivo studies demonstrate poor standardization of the included teeth using either direct external measurement or two‐dimensional radiographic techniques; this prevents appropriate matching of the sample selection in respect of pulp chamber volume or the residual thickness, height and volume of dentine (Corsentino et al, 2018; Ivanoff et al, 2017; Krishan et al, 2014; Marinescu et al, 2020; Maske et al, 2021). Furthermore, some studies fail to describe how the included sample selection were chosen at all (Chlup et al, 2017; Makati et al, 2018; Mustafa et al, 2020; Reddy et al, 2020). To highlight the relevance of this point, studies carried out using micro‐CT for accurate sample selection matching, as well as pre‐ and post‐experimental assessment of pulp chamber volume, dentine thickness, height and volume, consistently show no difference in the fracture resistance of teeth prepared with minimally invasive access cavities (Augusto et al, 2020; Barbosa et al, 2020; Lima et al, 2021; Rover et al, 2017).…”
Section: Contributory Risk Factorsmentioning
confidence: 99%